Novel stretchable thermochromic transparent heaters designed for smart window defroster applications by spray coating silver nanowire - Veeramuthu, Loganathan; Chen, Bo-Yu; Tsai, Ching-Yi; Liang, Fang-Cheng; Venkatesan, Manikandan; Jiang, Dai-Hua; Chen, Chin-Wen; Cai, Xingke; Kuo, Chi-Ching (RSC advances, 2019)
A productive and novel method for fabricating stretchable transparent heaters with recognised thermochromic properties using commercially available thermochromic ink (TM-55-blue) and silver nanowire (AgNW)-coated polydimethylsiloxane (PDMS) is proposed. Lower resistance, elevated heat generation, and higher transparencies were the expected essential prerequisites for the fabrication of items such as smart windows and window defrosters. AgNW-coated PDMS (hereafter PH devices) satisfied the essential prerequisites but did not produce sufficient color change. In addition to the appreciable electrical and optical characteristics and mechanical robustness, observable color changes represent a critical factor in effortless temperature monitoring by the heating device. Blending TM-55-blue thermochromic ink with PDMS (PBH device) improves the heating rate and color transformation and promotes the ultralow response time appreciably. More notably, it produces a visible transformation from blue to colorless. Color changes visible to the naked eye, ultralow response time, and heating rate represent valuable features for deploying the PBH devices as window defrosters and in smart window applications. The as-designed heaters proved to be excellent candidates for employment in window defrosters, as they satisfy the essential prerequisites such as lower sheet resistance, high transparency, mechanical robustness and good stability to tensile strain.